Evaluation of bistatic intersystem interference due to scattering by hydrometeors on tropical paths - Ajewole, Oludare; Kolawole, L.B; Ajayi, G.O (International Journal of Satellite Communications, 2020)
International Journal of Satellite Communications Vol.17NO5,P.339-356 ·